2013
DOI: 10.1108/oir-03-2011-0182
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of user generated content quality in Wikipedia

Abstract: Purpose -Social media platforms allow near-unfettered creation and exchange of user generated content (UGC). Drawing from network science, the purpose of this paper is to examine whether high and low quality UGC differ in their connectivity structures in Wikipedia (which consists of interconnected user generated articles). Design/methodology/approach -Using Featured Articles as a proxy for high quality, a network analysis was undertaken of the revision history of six different language Wikipedias, to offer a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…A study of the WikiProject Medicine revealed a strong positive correlation between new collaborative content and readership, pointing to the dissemination power of collaboration (Ransbotham, Kane & Lurie, 2011). This is supported by the study by Masterman and Wild (2011) Albeit having the potential to eliminate creation and distribution costs, usergeneration still raises quality and information reliability questions (Ingawale, Dutta & Seetharaman, 2013). However, Pratham Books' Chairperson argued that in a context where learners have low levels of literacy and limited or no access to resources, the mere availability of any resource is beneficial to their development (S. Singh, personal communication, May 18, 2016).…”
Section: Anything That Is Free May Not Have a Value (Kumar) The Promentioning
confidence: 77%
See 4 more Smart Citations
“…A study of the WikiProject Medicine revealed a strong positive correlation between new collaborative content and readership, pointing to the dissemination power of collaboration (Ransbotham, Kane & Lurie, 2011). This is supported by the study by Masterman and Wild (2011) Albeit having the potential to eliminate creation and distribution costs, usergeneration still raises quality and information reliability questions (Ingawale, Dutta & Seetharaman, 2013). However, Pratham Books' Chairperson argued that in a context where learners have low levels of literacy and limited or no access to resources, the mere availability of any resource is beneficial to their development (S. Singh, personal communication, May 18, 2016).…”
Section: Anything That Is Free May Not Have a Value (Kumar) The Promentioning
confidence: 77%
“…This chapter discussed some of those key problems starting with the proliferation of volunteer and user-generated content (Mallapragada et al, 2012), which despite being a solution to existing distribution problems, poses significant quality concerns (Ingawale et al, 2013). Several studies indicate that quality plays a major role in the sustainability of an OER project (Clements & Pawlowski, 2012;Cechinel et al, Tate & Hoshek, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations